Adaptation of Metabolomics and Microbiomic Research Protocols During the COVID-19 Pandemic. Issue 2 (March 2022) - Butts, Brittany; Alford, Taqiyya; Brewster, Glenna; Carlson, Nicole; Coleman, Ebony; Davis, Erica; Ferranti, Erin; Kimble, Laura P.; Narapareddy, Laren; Wells, Jessica; Yang, Irene
Abstract : Background: When the COVID-19 pandemic hit in 2020, researchers in the P30 Center for the Study of Symptom Science, Metabolomics, and Multiple Chronic Conditions at Emory University's Nell Hodgson Woodruff School of Nursing faced major challenges in recruitment and data collection because of limited access to the clinic and community facilities and the risk of COVID-19 exposure associated with in-person study contact. Objectives: The purpose of this article is to (a) describe how a cadre of pilot/supplement principal investigators adapted their studies to allow for safe and trustworthy data collection during the COVID-19 pandemic (March 2020 through date of publication) and (b) discuss steps that facilitated the technical aspects of remote data collection, especially involving biological specimens. Results: Four pilot studies and two administrative supplements within the center—all at different stages of execution—adopted various alternative remote recruitment, enrollment, and data and specimen collection approaches to continue their research endeavors in a way that maximized the safety of both the research participants and the research teams. Discussion: The article concludes with a discussion on the importance of a participant-centered approach when using remote methods, actions, or steps initiated to facilitate the technical aspects of remote data collection and reflections on the continued use of remote research strategies beyond the COVID-19 pandemic. Abstract : Supplemental digital content is available in the text.